2018
DOI: 10.3233/wor-172657
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and work-related stress in Italian rehabilitation professionals: A comparison of physiotherapists, speech therapists and occupational therapists

Abstract: Like all health care workers, rehabilitation professionals are at a high risk of burnout. There are common mechanisms underlying burnout in the different professional groups investigated. Further research in occupational health in rehabilitation settings is needed to prevent burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 26 publications
9
63
1
7
Order By: Relevance
“…Another relevant factor is the type of working hours, where it was found that the professionals with split shifts manifested a higher percentage of burnout than those who worked in morning or afternoon shifts. This finding was expected, and can be connected with another study where there was a significant correlation between the risk of exhaustion and prolonged work hours [24].…”
Section: Discussionsupporting
confidence: 83%
“…Another relevant factor is the type of working hours, where it was found that the professionals with split shifts manifested a higher percentage of burnout than those who worked in morning or afternoon shifts. This finding was expected, and can be connected with another study where there was a significant correlation between the risk of exhaustion and prolonged work hours [24].…”
Section: Discussionsupporting
confidence: 83%
“…Gisbert et al (2008) reported that only 4% of the surveyed Spanish physiotherapists reported burnout. Bruschini et al (2018) have reported that 15.7% of the surveyed Italian physiotherapists are at high risk of developing burnout, Śliwiński et al (2014) reported that 22.5% of the surveyed Polish physiotherapists evidenced high levels of burnout and Schuster, Nelson, and Quisling (1984), reported a prevalence of burnout of 53% in American physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…This line of thought considers exhaustion to have a central role in the process, and in fact exhaustion is a key dimension in all theoretical perspectives of burnout. Exhaustion is the most widely reported and analysed component of the syndrome and, although this approach is not consensual (Maslach, Leiter, & Schaufeli, 2008), emotional exhaustion has been reported as the most prominent burnout characteristic in studies enrolling health professionals in general (Bruschini, Carli, & Burla, 2018) and physiotherapists in particular (Wandling & Smith, 1997), highlighting the importance of this component.…”
Section: Burnout In Portuguese Physiotherapists Prevalence and Influmentioning
confidence: 99%
“…When one tries to define SB one can find a multiplicity of definitions in this respect. Currently, most of the studies are framed within the three-dimensional approach that the syndrome is composed of emotional exhaustion, depersonalization and loss of self-fulfilment in the workplace (Martínez-Moreno et al, 2020;Pires and Ugrinowitsch, 2020;Li, et al 2018;Mikalauskas et al, 2018;Kavanagh et al, 2018;Armenta-Hernández et al, 2018;Bruschini et al, 2018;Kawamura et al, 2017;Leiter and Maslach, 2017) and in the case of students the three dimensions are: emotional exhaustion, cynicism and academic effectiveness or selfefficacy (Liu et al, 2018;Boni et al, 2018;Erschens et al, 2018;Liébana-Presa et al, 2017;Hederich-Martínez et al, 2016;Tomaschewski et al, 2014) University students, like any professional, are faced with the pressures and overloads of academic work.…”
Section: Introductionmentioning
confidence: 99%